Analisis Pemerintah Kecamatan Kencong dalam Penertiban Area Pedagang Kaki Lima (PKL) untuk Meningkatkan Penjualan di Alun-Alun Kecamatan Kencong Jember - Yoga Alvan Hadaina; Dovi Iwan Habibillah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This analysis discusses the efforts of the Kencong Sub-District Government in regulating the Pedagang Kaki Lima (PKL) area to enhance sales at the Kencong Sub-District Square in Jember. This study explores the role of the informal sector, such as PKL, in reducing unemployment amidst high urban unemployment rates. The phenomenon of the informal sector, including PKL, is a crucial part of the economy in developing countries like Indonesia. The research employs a review method with a qualitative approach to analyze data from various sources, including academic journals, books, media articles, and related documents. The analysis results indicate that regulating the PKL area in Kencong Sub-District requires strategies involving the provision of strategic locations, improvement of facilities and infrastructure, and enhancement of cleanliness and security services. Despite the positive steps taken by the government, there are still obstacles in organizing and developing PKL, as well as challenges in relocating vendors to designated areas. The response of vendors to the regulation policy varies; some support it with the condition of fair treatment and consideration for the vendors' well-being, while others view it as a positive step to enhance the area's attractiveness. In conclusion, regulating the PKL area requires solutions that consider the sustainability of trading activities and the well-being of vendors, and it needs to be carried out with awareness and effective solutions from the government.